(untitled) (Historia, 2021)
The Great War in Great War was chiefly the concern of the British community. The war effort in the province was entirely in the hands of English-speaking settler elite, which, as we shall see, displayed great diligence and zeal in the imperial cause. This is the thesis of this article on the Natal home front during the First World War. The article is also an assay of published sources on the topic. It is not a work of original research, but a survey of primary and secondary literature, which is remarkably sparse and fragmentary (as the notes will indicate) in spite of the significance of the subject, and therefore it marks a starting point for further research in the field on the eve of the centenary.